2019
DOI: 10.1371/journal.pone.0210368
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis of viruses in toilet waste from long distance flights—A new procedure for global infectious disease surveillance

Abstract: Human viral pathogens are a major public health threat. Reliable information that accurately describes and characterizes the global occurrence and transmission of human viruses is essential to support national and global priority setting, public health actions, and treatment decisions. However, large areas of the globe are currently without surveillance due to limited health care infrastructure and lack of international cooperation. We propose a novel surveillance strategy, using metagenomic analysis of toilet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 59 publications
(66 reference statements)
0
34
0
Order By: Relevance
“…However, such studies have only focused on a single or a limited number of the possible pathogens found in sewage. Despite metagenomics being in its infancy, several recent studies have shown the feasibility of this methodology to identify and quantify a wide range of bacteria, viruses, and antimicrobial resistance (AMR) genes from complex samples such as sewage and wastewater [5,[7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…However, such studies have only focused on a single or a limited number of the possible pathogens found in sewage. Despite metagenomics being in its infancy, several recent studies have shown the feasibility of this methodology to identify and quantify a wide range of bacteria, viruses, and antimicrobial resistance (AMR) genes from complex samples such as sewage and wastewater [5,[7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, with the real picture of the virome in mind, vertebrate viruses are commonly found in low proportions with respect to other viruses such as bacteriophages and plant viruses, which have been described as the most abundant in sewage samples [65,88]. TES has been successfully employed in previous studies [21,49,50,67,68] to improve the detection of vertebrate viruses of interest that would otherwise be difficult due to their low concentrations in environmental samples. Recently, the VirCapSeqVERT Capture Panel was applied in a metagenomic study to evaluate NoV genomic diversity in oysters [50], but to date, no studies have applied this capture approach to fresh fruits and vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…Libraries were equimolarly pooled and captured using the VirCapSeqVERT Capture Panel (Roche, Basel, Switzerland). This panel involves the hybridization of probes designed to capture sequences from vertebrate viral pathogens, and it has enabled the detection of viral sequences in complex sample types in previous studies [21,49,50,67,68]. After the capture, quality and concentration were checked, and captured libraries were sequenced using an Illumina MiSeq 2 × 300 bp platform.…”
Section: Capture Of Viral Sequences By Vircapseq-vert Capture Panelmentioning
confidence: 99%
“…Areas encompassed by computational biology depend on the specific goals and the types of experimental data that are available, including sequence and structural analysis [60,61] and their correlation with function [62], evolution and population genomics, regulatory [63] and metabolic networks [64], image analysis [65], and disease [66]. Computational biology often addresses tasks by analyzing large genomic [67,68,69,70,71], proteomic, microarray, cell and tissue imaging, and clinical data [72,73] to produce robust statistical trends and correlate these with outcomes. It harnesses high-throughput genomic and proteomic methods to integrate data [74], to identify and validate biomarkers and novel therapeutic targets, and to rapidly translate the findings to the clinic.…”
Section: The Breadth Of Computational Biologymentioning
confidence: 99%